A man of many flags : memoirs of a war crimes investigator - Bassiouni, M. Cherif, 1937-2017 (Chicago : Hart Publishing, an imprint of Bloomsbury Publishing, 2020)
"M Cherif Bassiouni was a towering figure in international law. He was personally connected to some of the most historically relevant moments of the past century: the Suez War; the Camp David Accords; the fall of Muammar el-Qaddafi in Libya and the establishment of the International Criminal Court. A true global citizen - raised in Egypt, educated in Europe and emigrated to the United States - his life cut across cultures and religions. This fascinating memoir gives an immediate and personal eye-witness account of the operation of international events during a tumultuous period"--
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Criminal investigation (International law); War crimes investigation; Wars -- Personal narratives; International law; Electronic books